SOYBEAN SEED QUALITY STORED IN DISTINCT CONDITIONS OF TEMPERATURE AND RELATIVE HUMIDITY - TOSIN, José Cavassin (Scientia Agraria, 2002)
The present work was done in the Laboratory of Seed Pathology of the Department of Fitotecnia and Fitossanitarismo of the Federal University of Paraná, in the air, in the period from January to July of 2000, with the objective to evaluate the effects of the temperature and relative humidity of the air, in the pathogen incidente in soybean seeds submitted to different storage periods. The experiment was set up in a complete randomized design with treatments in a factorial 3 x 4 x 5, being three temperatures (25ºC, 30ºC and 35ºC) four levels of relative humidity of the air (RH%) (50%, 65%, 75% and 85%) and five storage periods (30, 60, 90, 120 and 150 days), with four replications, using soybeans seeds of the cultivar Xingú, coming from the State of Mato Grosso. The initial determination of the seed quality was accomplished by the tests of germination, accelerated aging, tetrazolium and pathology by means of the Blotter test. It was also determined the initial moisture content of seeds. For the subsequent evaluations, approximately 300g of seeds were conditioned in nylon bags and placed in flasks of two liters, with controlled RH. The values of RH% were obtained by ways of using glycerin solution in sterilized water in different weight proportions. The flasks were placed in three germination cameras, each one of them with one of the three temperatures used. At 30, 60, 90, 120 and 150 days, samples of 500 seeds were taken of all the treatments, for accomplishment of the pathology, germination and the moisture content tests. It was concluded that; RH% of 75 and 85% combined with the three temperature elevated the moisture content of seeds to values in that there is risk of fast deterioration; that for a safe storage, in that the seeds stay with a moisture content that avoids fungal and bacterial growths besides preserving good germination, the temperature should be of 25ºC and 65% RH. It was also concluded that with increase of the storage period, it happens an increase in the incidence of storage fungi, unlike what it happens with the field fungi, which tend to disappear.